The Profile of Outcome Patient Response to The Quality of Drug Information Services in Medicine Rooms at Mamajang Puskesmas - H. Ambo Lau, Sulfiyana; Herman, Herman (Politeknik Sandi Karsa, 2021)
The pharmacist should always provide maximum drug information services to the patients in order that the information they got will not be hesitate with the medicine they will consume. The research has been done related to the profile of the outpatients’ satisfaction at Mamajang public health center toward the quality of drug information services. The aim of this research is to know the profile of the outpatients’ satisfaction at Mamajang public health center toward the quality of drug information. This research used descriptive method. The data were obtained by collecting the result of the answers from questionnaires with 10 questions than make tabulation, scoring then presented, where the total of samples were got as many as 96 respondents with rating scale Likert namely: satisfied, quite satisfied, not satisfied. Based on the result of the research, it can be inferred that outpatients at Mamajang public health center felt satisfied with the drug information services which is given by crew of public health center in this case on the part of pharmacist itself with percentage 85,24%.